Identifying the effects of monetary policy shocks on exchange rates using high frequency data - Jon Faust; John H. Rogers; Eric Swanson; Jonathan H. Wright (European Central Bank (ECB), 2002)
This paper proposes a new approach to identifying the effects of monetary policy shocks in an international vector autoregression. Using high-frequency data on the prices of eurodollar contracts, we measure the impact of the surprise component of the FOMC-day Federal Reserve policy decision on financial variables, such as the exchange rate and the foreign interest rate. We show how this information can be used to achieve identification without having to make the usual strong assumption of a recursive ordering.
Keywords: C32; E52; F30; 330; Exchange Rates; High Frequency Data; Identification; monetary policy; Vector autoregression